Hidden costs of taxation - Sandford, Cedric T.; The Institute for Fiscal Studies (London : The Institute for Fiscal Studies, 1973)
Successive governments have promised to reduce business red tape, whilst doing nothing about it. In fact, with regard to the tax system, ever-greater numbers of taxes and ever-greater complexity have increased burdens on business. This book shows that this should not be the case, and propose ways of reducing the burden of tax bureaucracy.
aia 11/03/2019
Loans
Keywords: Taxation--Compliance costs; Great Britain